2015
DOI: 10.1371/journal.pone.0123814
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HIV Testing Is Highly Acceptable and Preferred among High-Risk Gay And Bisexual Men after Implementation in Sydney Sexual Health Clinics

Abstract: BackgroundRapid HIV testing (RHT) is well established in many countries, but it is new in Australia. We assessed the acceptability of RHT and its associations among gay, bisexual and other men who have sex with men (GBM) after implementation of RHT in Sydney sexual health clinics.MethodsGBM were invited to complete an acceptability questionnaire before and after provision of the result of finger-prick blood RHT, comparing their experience of RHT with conventional HIV testing (CHT) involving venipuncture. Logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…model. The high acceptability observed in this study is consistent with other Australian studies reporting high acceptability of RPOC testing in clinical settings [ 22 , 32 ]. However, relative to PRONTO!…”
Section: Discussionsupporting
confidence: 91%
“…model. The high acceptability observed in this study is consistent with other Australian studies reporting high acceptability of RPOC testing in clinical settings [ 22 , 32 ]. However, relative to PRONTO!…”
Section: Discussionsupporting
confidence: 91%
“…Rapid test performance was compared with the standard of care laboratory serology assays used in this setting and patient and staff acceptability were assessed via surveys. Our data on test performance and the acceptability of HIV POCT to patients and providers have previously been published [ 24 – 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…All participants reported that they would like to test for HIV using this method again (ie, at home testing with peer counseling via video chat) and that they would recommend to their friends this method of HIV testing and counseling. These findings suggest that this HIV testing and counseling approach is well-received by MSM, which points to its potential to make an impact on improving HIV testing uptake and frequency among this higher risk population [30]. These findings warrant support for further study of at-home HIV testing and peer counseling via video chat.…”
Section: Discussionmentioning
confidence: 90%